The influence of academic library staff body language on library users during initialization and negotiation - Paule, Dominique C.; Santos, Herminia H. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
This study concerned itself with three main areas regarding body language and the role that it plays in the communication process that takes place within the library framework. Primarily, the study examined whether library users are affected by academic library staff (ALS) body language such that they become hesitant to approach them and/or uneasy while interacting with them. In cases where library users do become hesitant to approach and/or uneasy to interact because of ALS body language, the study examined to what degree are the library users affected. Lastly, the study attempted to clarify the aforementioned influence of ALS body language by examining whether the gender or age of library users intervene in the way they are affected by ALS body language.
A survey questionnaire was used to gather the necessary data for this study. All 200 questionnaires distributed were returned. Using the questionnaire's filter mechanisms, 63 (31.5 percent) of the returned questionnaires were rejected. Respondents for this study consisted of individuals who have used the UP Main Library at least once. For the purpose of analysis, respondents were classified into four groups: males 20 below and 21 above; females 20 below and 21 above.
The data gathered is primarily presented through tabulated frequency distributions. Preliminary analysis of data was done through the examination of modal frequencies in these tables. Log-linear modeling was used to address the third area with which this study is concerned. Using the log-linear modeling framework, independence models were examined to determine which variable (gender or age of library users) is a stronger intervening factor in the way library users are affected by ALS body language. Modal distributions show that a significant percentage of library users become hesitant to approach and uneasy to interact with an ALS during initialization and negotiation due to ALS body language. In cases where library users become hesitant to approach and uneasy interacting with an ALS, library users are more affected by ALS body language during initialization. Female library users are generally more sensitive to ALS body language during both initialization and negotiation contexts. On the other hand, similar percentage of library users aged 20 below and 21 above are made hesitant and uneasy because of ALS body language. As for the degree of library users' hesitance and uneasiness by age, younger library users tend to be more sensitive to ALS body language during both initialization and negotiation while older library users tend to ignore hesitance when approaching ALS and when interacting with them.
Examination of independence models show that gender is a stronger intervening factor than age in determining who among library users become hesitant to approach an ALS or uneasy in interacting with an ALS due to ALS body language. Age, on the other hand, exerts more influence than gender in determining to what extent or degree library users are affected by ALS body language during both initialization and negotiation.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Academic librarians -- Philippines -- Quezon City; Body language